Міжнародні та вітчизняні реалії функціонування індустріальних парків - Лекарь, С.І. (Економіка промисловості, 2017)
Досліджено світові тенденції функціонування індустріальних парків та застосування податкових стимулів для їх розвитку. Проаналізовано стан індустріальних парків в Україні, а також законодавчі ініціативи щодо оподаткування їх діяльності. Наведено ключові етапи створення та перелік основних ознак, за якими та чи інша відокремлена цілісна земельна ділянка може стати індустріальним парком. Исследованы мировые тенденции функционирования индустриальных парков и применения налоговых стимулов для их развития. Проанализировано состояние индустриальных парков в Украине, а также законодательные инициативы относительно налогообложения их деятельности. Приведены ключевые этапы создания и перечень основных признаков, по которым тот или иной отделённый целостный земельный участок может стать индустриальным парком. Industrial parks are legally separated coherent lands intended to accommodate industrial production. They often (but not always) are subject to special regimes of economic activity and in some cases special tax regimes. Their number in the world is exponentially increasing. Such popularity is explained by increasing of investment activity in the economy as the essence of the functioning of industrial parks is to attract investment generally in the high-tech manufacturing.Thus, industrial parks have become a tool of sustainable industrial development, attracting investment, increasing of employment, improving of competitiveness of a particular region, development of social infrastructure, increasing of local revenues and a positive image of the region by producing high quality and competitive products. Moreover, functioning of industrial parks in Ukraine will bring national products to the world market and increase investors trust through transparency and simplicity in business operations, which will be achieved by condition of the overall reform. So, as a conclusion we can say that the idea of using of industrial parks is very perspective and economically beneficial for companies and for the state. Proof of this is the international best practice of industrial parks functioning. Therefore, the existence of legal registration of industrial parks and legislative draft that appeals to taxation is a first step to further attraction of investors, that will provide high technology manufacturing, social projects for the population and improve the research capacity of the particular country. However, when creating industrial parks the features and characteristics of the object must be taken into account, which further minimizes (1) the possibility of loss-making situations (business interests) and (2) the size of the tax evasion (the interests of the state).Today industrial parks are new for Ukrainian practice but it is a perspective approach for the economic development of Ukraine. In such a case having successful international experience of industrial parks functioning the law-makers do not need to introduce something new, they just need to use best world practice extrapolating it to local realities.